Building A Leading Personality Through Sunnah of Prophet Peace Be Upon Him -Objective Study - Ahmed Mahmood Saydok; Luqman Samad Khudhur (QALAAI ZANIST JOURNAL, 2020)
This study aims to clarify (Building a leading personality through the Sunnah of Prophet peace be upon him -objectve study-), the study contains the definition of leading personality literally and technically, it also covers the necessity and importance of leading personality’s existence to through the Sunnah of Prophet peace be upon him always and everywhere. Because the Ummah are in dire need to the leading personality’s entity that could lead people to the blessing and goodness in this life and hereafter. The study also focuses on explaining and illustrating the methods and roper ways to build a leading personality through the teachings of Sunnah of Prophet peace be upon him, and his implementation for those teachings, whether from the faith, thoughts, and rational phase, or through building a positive thinking among the leaders, or through training and qualifying the leaders for a better organizing and management, as well as to act in a proper way and aware of self-control and emotions. The research explained the qualities and characteristics that differentiate Muslim leaders form others in many aspects, such as; monotheism and believing in Allah, following his prophet, self-purification, appointment of Muslim people as a successor on earth. The research paper tries to highlight all points that been discussed above by returning to Sunnah and deriving it from Sunnah contexts and prophet’s attitude peace be upon him with the great leaders among his companions throughout his life, this could be done through going back to the resources of Sunnah and the biography books of the prophet peace be upon him. The study conducted that the Sunnah is concentrating significantly on building a leading personality, there are remarkable number of Prophet’s saying peace be upon him, which focusing on a leading personality, when explain and indicate the leading personality’s characteristics and enlightening his methods, trainings and attitudes in every situation that he was facing, Sunnah has set a comprehensive method to create leaders in the Ummah, which is represented in several aspects in a particular leader, such as; ideological, rational, educational and professional phases, with this method the Prophet peace be upon him has created hundreds of great leaders who were able to make a considerable history and they served Islam and Muslims, as well as they have offered the world a great civilization and remarkable services. Sunnah has considered the leaders and the way that could guide and protect them to use their capacities and power to create themselves first and then to serve their religion and the Muslim Ummah.